Peran Komunikasi Pada Komunitas Bengkulu Beatbox Clan Dalam Memperkenalkan Musik Beatbox - Mohammad Tri Hidayatullah; Eceh Trisna Ayuh (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2022)
Beatbox is a melodic fine art that spotlights on delivering cadenced sounds and rhythms, instruments, as well as impersonations of different sounds, for example, the sound of water beads, large motorbikes, robot sounds, strides, and particularly turntable sounds, through human discourse organs like the mouth, tongue, lips, and other discourse holes. This study means to decide the job of correspondence in the Bengkulu Beatbox Clan Community in Introducing Beatbox Music. The technique utilized is a subjective strategy and utilizations graphic information investigation. This study utilizes Laswell's Communication hypothesis which has 5 focuses, in particular 1. Who?, 2. Expresses out loud Whatever?, 3. In Which Channels?, 4. To Whom, 5.With What Effect?. The aftereffects of the review make sense of that theBengkulu Beabox Clan community in introducing beatbox music is by introducing the community by carrying out activities in the context of Beatbox and outside of Beatbox because introducing community identity with various activities is one strategy to attract members interest. Key Word: Communication, Beatbox, Bengkulu Beatbox Clan Community